THE IMPORTANCE OF HIGHER EDUCATION - Madirimova Gulmira Kamoladdin qizi (Zeta Repository, 2023)
Higher education presents a wide range of options for further academic excellence serving as an enabler for broad specializations in careers, a pathway for career advancement, personal development, and overall socio-economic development. While many individuals believe that the primary motivation for attending higher education is to become more employable, the benefits are not limited to just that. This article will effectively examine the importance of higher education in society distilling the advantages as it relates to employability, personal growth, and societal development.